The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1744-9081-10-19
|View full text |Cite
|
Sign up to set email alerts
|

The neural mobilization technique modulates the expression of endogenous opioids in the periaqueductal gray and improves muscle strength and mobility in rats with neuropathic pain

Abstract: BackgroundThe neural mobilization (NM) technique is a noninvasive method that has been proven to be clinically effective in reducing pain; however, the molecular mechanisms involved remain poorly understood. The aim of this study was to analyze whether NM alters the expression of the mu-opioid receptor (MOR), the delta-opioid receptor (DOR) and the Kappa-opioid receptor (KOR) in the periaqueductal gray (PAG) and improves locomotion and muscle force after chronic constriction injury (CCI) in rats.MethodsThe CCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(76 citation statements)
references
References 57 publications
3
67
0
6
Order By: Relevance
“…(5) NM demonstrated efficiency in prevention of hypertrophy, muscular strength gains, improved nerve conduction velocity and reduction of pain in animals. (6,7) Whereas in humans were evidenced gains of flexibility and range of motion, pain relief, increase in the recruitment of muscle fibers, improve in neural conduction velocity, increase in the muscle strength and improve in the functionality. (8)(9)(10)(11)(12)(13) Although the explored studies have shown positive results, researchers still have antagonistic thoughts regarding the clinical applicability of NM.…”
Section: Introductionmentioning
confidence: 99%
“…(5) NM demonstrated efficiency in prevention of hypertrophy, muscular strength gains, improved nerve conduction velocity and reduction of pain in animals. (6,7) Whereas in humans were evidenced gains of flexibility and range of motion, pain relief, increase in the recruitment of muscle fibers, improve in neural conduction velocity, increase in the muscle strength and improve in the functionality. (8)(9)(10)(11)(12)(13) Although the explored studies have shown positive results, researchers still have antagonistic thoughts regarding the clinical applicability of NM.…”
Section: Introductionmentioning
confidence: 99%
“…Exercise and other forms of physical therapy are approved therapeutic treatment strategies in the rehabilitation of patients suffering from chronic pain including low back pain (Heneweer et al, 2009;Hooten et al, 2012;Babatunde et al, 2017;Geneen et al, 2017). Physical therapy reduces pain reactions in animals (Cobianchi et al, 2010;Shen et al, 2013;Sluka et al, 2013;Santos et al, 2014;Lima et al, 2017) and pain in humans (Naugle et al, 2012;Babatunde et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing male Wistar rats and Western blot assays of the PAG, Santos et al (2014) examined the brains of rats following neural mobilization for mu-, delta-, and kappa-opioid receptor expression. Researchers did not find changes in delta-and mu-opioid receptor expression following neural mobilization, but kappa-opioid receptor expression underwent a significant increase, by 17%.…”
Section: Neural Mobilizationmentioning
confidence: 99%